Management of Toxicity and Side Effects of Systemic Therapy for Renal Cell Carcinoma - Kate Young; Andreas M. Schmitt; Deborah Mukherji; Lavinia Spain; Manuela Schmidinger; Lisa M. Pickering (Société Internationale d’Urologie Journal)
Standard approved systemic treatment options for the management of renal cancer have entirely transformed in the last 15 years and now comprise molecularly targeted therapies against the vascular endothelial growth factor receptor (VEGFR) and the mammalian target of rapamycin (mTOR) as well as immune checkpoint inhibitors. These agents may be used alone as monotherapies but increasingly are used in various combinations. The associated important improvements in cancer control and survival have therefore been accompanied by a range of new toxicities. Good management of these toxicities is important for patient safety and quality of life, and also to optimize patients’ opportunity to continue with and therefore benefit from these therapies. The most common toxicities associated with VEGFR tyrosine kinase inhibitors are fatigue, skin rashes, gastrointestinal, stomatitis, hypertension and other cardiovascular toxicities, and hematological and endocrine dysfunction. Common side effects of mTOR inhibitors include asthenia, stomatitis, skin rashes, pneumonitis, metabolic changes and infections. Checkpoint inhibitors can lead to toxicities of any organ system with those seen most frequently including dermatologic, gastrointestinal and hepatic, endocrine, musculoskeletal, and pulmonary, whilst renal, hematological, ophthalmic, cardiac and neurological toxicities are seen less often. In general terms, toxicity management should start preemptively with patient education and may also include a combination of supportive approaches, dose reduction, schedule alteration, treatment interruption and occasionally treatment cessation. Treatment of individual toxicities is dependent on the likely causative agent and is guided by its grade or severity. Specific recommendations for management are discussed in this chapter.